Transient therapeutic communities: the "living-learning experience" trainings. Issue 2 (13th June 2016) - Lees, Jan; Haigh, Rex; Lombardo, Aldo; Rawlings, Barbara
Abstract : Purpose: – The purpose of this paper is to describe transient therapeutic communities (TCs) and their value for training. Design/methodology/approach: – This is a descriptive account which includes the findings of two field study evaluations, and direct participant feedback. It is an exploration of the application of TC and group analytic theory to transient TCs. Findings: – The transient TC format is an excellent training format for creating a powerful and effective environment for learning and personal development in the very short time frame of three days. Practical implications: – These courses are a very efficient and effective way of promoting reflective practice, enabling environments, and emotionally safe working practices. The trainings are useful for a wide range of people from mental health professions, those working in human resources, and those in senior positions in industrial, commercial and public sector fields. Social implications: – This paper will raise awareness that target-driven training is insufficient to improve quality of services beyond a certain point. A relational focus of training is needed to deal with issues of complexity which cannot be resolved by simple managerial methods. This experiential training can help to meet the need for inculcating compassion, kindness, and empathy in its participants. Originality/value: – Although other psychotherapy and group relations courses exist, and are used beyond the mental health field, the focus on generating an experience of belonging, emotional safety and democratic empowerment in the relational field of the course itself – by use of TC methodology – is novel, and could be of considerable value more widely.